A three-factor structure of cognitive functioning among carriers and non-carriers of autosomal-dominant Alzheimer’s disease - Guzmán-Vélez, Edmarie (J Alzheimers Dis, 2018)
OBJECTIVE: There is a need to find cognitive markers that can help identify individuals at risk for Alzheimer’s disease (AD), and that can be used to reliably measure cognitive decline. We tested whether a theoretically driven three-factor structure would characterize cognitive functioning in individuals who are genetically-determined to develop AD due to a mutation in Presenilin-1 (PSEN1) gene. We also examined whether these factors could distinguish cognitively unimpaired PSEN1 mutation carriers from age-matched non-carrier family members. METHOD: 1395 cognitively unimpaired members of a Colombian kindred with the PSEN1 E280A mutation were included in the study. A confirmatory factor analysis examined the fit of the three-factor model comprising episodic memory (MMSE memory recall, CERAD-COL Word list recall and Constructional praxis recall), executive function (Phonemic fluency and WCST perseverative errors), and psychomotor processing speed (TMT-A and WAIS-III Digit Symbol). RESULTS: The three-factor model provided an excellent fit for all participants (p=.24;RMSEA=.01). Further, the episodic memory (p=.0004,d=0.25) and executive functioning (p=.001,d=0.18) factors distinguished cognitively unimpaired carriers from non-carriers. The episodic memory factor provided the earliest indication of preclinical cognitive decline at 35 years of age, nine years before individuals’ estimated age of clinical onset. CONCLUSIONS: The three theoretically derived cognitive factors provide a reliable measure of cognition and may be useful for the early detection of AD, as well as for measuring disease progression. However, longitudinal studies are needed to confirm that these factors can be used to track the progression of cognitive decline in preclinical AD.